O estudo das cônicas a partir da construção geométrica - Lenz, Mainara [UNESP] (2014)
On high school courses the study of Conics starts with the de nition which leads to an equation and nally the picture of the conic is presented. In this work we shall introduce the Conics in a di erent approach. We will start with the construction using only ruler and compass based on some of its properties and then we will de ne Conics. Finally we will obtain its equation and its algebraic characteristics. We will start with some basic concepts which will guide us to the study of Conics: ellipse, hyperbole and parabola. Finally we will present a proposal of classes that we hope can be used by high school teachers